Ajaran Paulus Tentang Kebangkitan Orang Percaya Dalam I Korintus 15 : 1 – 58 - Bert Haniko (EUANGGELION: Jurnal Teologi dan Pendidikan Kristen, 2022)
The way of the cross is for the Lord Jesus Christ to atone for human sins. This is clearly the expression “Christ died  for our sins” (I Cor. 15:3). Next Paul emphasizes His resurrection on the third day (v. 4).This explanation gives an understanding that the cross and the resurrection of Jesus Christ cannot be separated from one another. Both are part of  God's great act with the goal of human salvation. Morris (1994: 116) quotes Walther Kunneth's view as follows: Jesus' death provided atonement and atonement, the "Lamb of God" became a punishment, a sacrifice, was crucified, an act in the place of another.